Retificação do aço AISI 4340 usando corte interrompido com rebolo convencional - de Mello, Hamilton Jose [UNESP]; de Mello, Diego Rafael [UNESP]; Bianchi, Eduardo Carlos [UNESP]; de Aguiar, Paulo Roberto [UNESP]; D'Addona, Doriana M. (My University, 2015)
There has been a great advance in the grinding process by the development of dressing, lubri-refrigeration and other methods. Nevertheless, all of these advances were gained only for continuous cutting; in other words, the ground workpiece profile remains unchanged. Hence, it becomes necessary to study grinding process using intermittent cutting (grooved workpiece – discontinuous cutting), as little or no knowledge and studies have been developed for this purpose, since there is nothing found in formal literature, except for grooved grinding wheels. During the grinding process, heat generated in the cutting zone is extremely high. Therefore, plenty of cutting fluids are essential to cool not only the workpiece but also the grinding wheel, improving the grinding process. In this paper, grinding trials were performed using a conventional aluminum oxide grinding wheel, testing samples made of AISI 4340 steel quenched and tempered with 2, 6, and 12 grooves. The cylindrical plunge grinding was performed by rotating the workpiece on the grinding wheel. This plunge movement was made at three different speeds. From the obtained results, it can be observed that roughness tended to increase for testing sample with the same number of grooves, as rotation speed increased. Roundness error also tended to increase as the speed rotation process got higher for testing the sample with the same number of grooves. Grinding wheel wear enhanced as rotation speed and number of grooves increased. Power consumed by the grinding machine was inversely proportional to the number of grooves. Subsuperficial microhardness had no significant change. Micrographs reveal an optimal machining operation as there was no significant damage on the machined surface.
Grinding of AISI 4340 steel with interrupted cutting by aluminum oxide grinding wheel
Keywords: Cutting power; External cylindrical plunge grinding; Finishing; Interrupted cut; Microhardness